An LC/MS/MS method for stable isotope dilution studies of β-carotene bioavailability, bioconversion, and vitamin A status in humans - Oxley, Anthony; Berry, Philip; Taylor, Gordon A; Cowell, Joseph; Hall, Michael J; Hesketh, John; Lietz, Georg; Boddy, Alan V (Journal of lipid research, 2014)
Isotope dilution is currently the most accurate technique in humans to determine vitamin A status and bioavailability/bioconversion of provitamin A carotenoids such as β-carotene. However, limits of MS detection, coupled with extensive isolation procedures, have hindered investigations of physiologically-relevant doses of stable isotopes in large intervention trials. Here, a sensitive liquid chromatography-tandem mass spectrometry (LC/MS/MS) analytical method was developed to study the plasma response from coadministered oral doses of 2 mg [(13)C10]β-carotene and 1 mg [(13)C10]retinyl acetate in human subjects over a 2 week period. A reverse phase C18 column and binary mobile phase solvent system separated β-carotene, retinol, retinyl acetate, retinyl linoleate, retinyl palmitate/retinyl oleate, and retinyl stearate within a 7 min run time. Selected reaction monitoring of analytes was performed under atmospheric pressure chemical ionization in positive mode at m/z 537→321 and m/z 269→93 for respective [(12)C]β-carotene and [(12)C] retinoids; m/z 547→330 and m/z 274→98 for [(13)C10]β-carotene and [(13)C5] cleavage products; and m/z 279→100 for metabolites of [(13)C10]retinyl acetate. A single one-phase solvent extraction, with no saponification or purification steps, left retinyl esters intact for determination of intestinally-derived retinol in chylomicrons versus retinol from the liver bound to retinol binding protein. Coadministration of [(13)C10]retinyl acetate with [(13)C10]β-carotene not only acts as a reference dose for inter-individual variations in absorption and chylomicron clearance rates, but also allows for simultaneous determination of an individual's vitamin A status.